Immunodeficiency syndrome in a Weimaraner involving the peripheral nervous system. Issue 1 (4th May 2016) - Cuthbert, S.; Morton, M.; Lowrie, M.
Abstract : An 11‐week‐old male entire Weimaraner presented with a five‐day history of pyrexia and pain. Onset of clinical signs developed within five days of routine second vaccination with a modified live multivalent vaccination. General clinical examination identified a diffuse swelling across the muzzle indicative of vasculitis and concurrent blepharoconjunctivitis. Orthopaedic examination demonstrated pain and swelling in multiple joints of both thoracic and pelvic limbs. Neurological examination demonstrated ambulatory flaccid tetraparesis with decreased segmental spinal reflexes indicating a diffuse neuromuscular localisation. Immunoglobulin (IgG, IgM and IgA) analysis was performed, suggesting an inherited immunodeficiency. Radiographs of multiple joints confirmed bilateral effusions and evidence of hypertrophic osteodystrophy, also known as metaphyseal osteopathy. Joint taps suggested the presence of polyarthritis with neutrophilic inflammation. Electrodiagnostics supported a polyradiculoneuritis. Immunosuppressive prednisolone was administered and a full recovery was achieved. This is the first report of peripheral nervous system involvement in a dog with immunodeficiency.